Fabrication of a coaxial high performance fiber lithium-ion battery supported by a cotton yarn electrolyte reservoir. (June 2019) - Song, Hyeonjun; Jeon, Seung-Yeol; Jeong, Youngjin
Abstract: Our report describes a coaxial fiber-type lithium-ion battery consisting of cotton core yarn wrapped with carbon nanotube (CNT) films and a nano-web separator. The CNT film was used as a current collector because of its high conductivity, flexibility, and network structure. The cotton yarn served as an electrolyte reservoir and a skeleton for the fiber shape. The cotton yarn even absorbed electrolyte as much as 9 times its own weight and its diameter swelled up to a 20%, which resulted in robust interfacial contact between components of the battery. Also, the swelling behavior of cotton yarn due to electrolyte up-take was simulated to clarify the function of cotton yarn. The nano-web separator was beneficial in accommodating the in-plane deformation occurred during the bending of the battery. This coaxial fiber battery exhibited stable performance even under bent or knotted states and delivered 144.82 mWhcm −3 of volumetric energy density with high coloumbic efficiency of about 95%. Successful demonstration of the flexible fiber battery bespeaks a promising future for wearable electronic devices. Graphical abstract: Image 1